Carbon and nutrient release during decomposition of coarse woody debris in forest ecosystems of Central Siberia - Mukhortova, Liudmila V. (Zenodo, 2012)
Coarse woody debris (CWD) is often overlooked in studies on the decomposition of organic matter in forest soils. To assess the role of CWD in carbon and nutrient cycling in these forest ecosystems, we investigated changes in carbon and nutrients of differently decomposed CWD samples from the forest tundra and northern, middle, and southern taiga of Central Siberia. Samples included live wood, snags, logs at the classes I, II, and III of decomposition, and fragments of decomposed wood from forest litter. At northern latitudes CWD released a larger amount of carbon and nutrients during decomposition compared with southern ecosystems, which were characterized by nutrient immobilization and smaller carbon losses from CWD. We conclude that CWD in northern and southern ecosystems probably plays a different role in biogeochemical cycles. Logs of pine, spruce, and fir in southern ecosystems accumulate significant amount of nutrients in their biomass during decomposition and create relatively nutrient-rich microsites. In contrast, CWD in northern ecosystems appears to be an important source of carbon and nutrient release to the soil solution.